Ratio Legis Pembentukan Daerah Otonom Baru Provinsi Pulau Sumbawa di Nusa Tenggara Barat - Ikbal; Taufik Firmanto; Amar Ma'arij (CV Rewang Rencang, 2025)
The establishment of Sumbawa Island Province as a new autonomous region (DOB) in West Nusa Tenggara reflects the spirit of decentralization and the aspirations of the community to achieve equitable development and efficient governance. This research uses a normative-juridical approach by examining relevant regulations, literature, and policy documents. The study shows that philosophically, the idea of ​​DOB is based on the principle of distributive justice, legally grounded in the 1945 Constitution and Law No. 23 of 2014, and sociologically supported by the demands of the Sumbawa Island community. However, administrative, economic, and human resource challenges demand a clear and sustainable development roadmap.